Reflexiones sobre El perro del hortelano de Pilar Miró - Mañas Martínez, María del Mar (Dicenda. Estudios de lengua y literatura españolas, 2003)
This essay offers some practical ideas about the 1995 Spanish movie El perro del hortelano directed by Pilar Miró. This film was extremely successful although it is based in a 1618 Lope de Vega comedia, a Seventeenth-Century drama characterized by its conceptual language and psychological depth. I explore the cinematographic strategies developed by Pilar Miró to express the representations of intimacy and humour in order to achieve public success without betraying the literary work that inspired her film.